Solid Waste Management: a study in a company that operates in the city of Xanxerê and region - Petry, David Rodrigo; Bortoluzzi, Citania Aparecida Pilatti; Sehnem, Simone; Oro, Ieda Margarete (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In the study presented here identified that form is held solid waste management in the city of Xanxerê and region by the Continental Works and Services Company, prioritizing know how the waste collected is intended. This is a case study with descriptive and qualitative procedures, analyzed through interviews, documents and direct observations at the company. This study enabled us to reveal that the solid waste management in the region where it operates the company meets current legislation, as well as possible to identify the company’s concern to use effective processes to reduce costs and improve quality of life and welfare of the population. It is concluded that the awareness of people involved and the practice of selective collection still in the households of the population, so there are improvements in the quality of waste management is necessary. Also identified the need for improvement in technology for screening materials through equipment with affordable cost, since the whole process is currently done manually.